Complete Genome Sequence of blaIMP–6-Positive Metakosakonia sp. MRY16-398 Isolate From the Ascites of a Diverticulitis Patient - Sekizuka, Tsuyoshi; Matsui, Mari; Takahashi, Tomiyo; Hayashi, Michiko; Suzuki, Satowa; Tokaji, Akihiko; Kuroda, Makoto (Frontiers in Microbiology, 2018)
A novel species of carbapenemase-producing Enterobacteriaceae (CPE) was isolated from a patient diagnosed with sigmoid colon diverticulitis. At first, laboratory testing suggested it was Klebsiella oxytoca or Pantoea sp.; however, a complete genome sequence of the isolate, MRY16-398, revealed that it could be novel species, most similar to [Kluyvera] intestini, of which taxonomic nomenclature is still under discussion. Orthologous conserved gene analysis among 42 related bacterial strains indicated that MRY16-398 was classified as the newly proposed genus Metakosakonia. Further, MRY16-398 was found to harbor the blaIMP-6 gene-positive class 1 integron (In722) in plasmid pMRY16-398_2 (IncN replicon, 47.4 kb in size). This finding implies that rare and opportunistic bacteria could be potential infectious agents. In conclusion, our results highlight the need for continuous monitoring for CPE even in nonpathogenic bacteria in the nosocomial environment.